The Role of Overseas Listing in the Chinese State-owned Commercial Bank Reform - LIAN, Chunhui (2007)
Overseas listing refers to the listing of shares of common stock on abroad stock exchanges rather than on domestic stock exchanges (FIU Edu, 2004). Recent years, an increasing number of firms prefer to overseas listing for larger financing. From 2004 to 2005, three main Chinese state-owned commercial banks-Banks of China (BOC), Chinese Construction Bank (CCB), Industrial and Commercial Bank of China (ICBC) have issued their shares in Hong Kong stock market since 2005 as well, which is considered as a big step of Chinese banking system reform. This paper makes a tentative study on the influence of overseas listing in solving such problems as weak corporate governance and poor financial performance of the three Chinese state-owned banks, and on this basis, aims to find out the role of overseas listing in Chinese commercial bank reform.